SIFAT KIMIA DAN ORGANOLEPTIK PATI SAGU (Metroxylon sago Rottb.) MODIFIKASI KIMIA DENGAN PERLAKUKAN SODIUM TRIPOLYPHOSPHATE (STPP) - Emilia Hasibuan; Faizah Hamzah; Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aimed of the research was to obtain the best combination for modified starch by STPP treatment. This study used Completely Randomized Design with 2 factor treatments, concentration of STPP (0,5%; 1% and 1,5%) and soaking time (1 hour, 1,5 hour and 2 hour) with 4 replications. Datas were analyzed by using ANOVA and DMNRT with significant level 5%. The result showed that concentration of STPP treatment gave significant effect in increasing moisture content and decreasing swelling power, but not gave significant effect to mineral content, solubility and organoleptic test. Treatment of soaking time not gave significant effect for moisture content, ash content, swelling power, solubility and organoleptic test. Interaction of both treatment not gave significant effect to not gave significant effect for moisture content, ash content, swelling power, solubility and organoleptic test. The best combination treatment is K3T3 with 1,5% of STPP and 2 hours soaking time. Keywords: Sago starch, chemical modification, starch modification, STPP